Effectiveness of influenza and pneumococcal vaccines on chronic obstructive pulmonary disease exacerbations. Issue 10 (15th June 2022) - Li, Yan; Zhang, Pingshu; An, Zhijie; Yue, Chenyan; Wang, Yamin; Liu, Yunqiu; Yuan, Xiaodong; Ma, Ying; Li, Keli; Yin, Zundong; Wang, Liye; Wang, Huaqing
Abstract: Background and objective: Single‐study evidence of separate and combined effectiveness of influenza and pneumococcal vaccination in patients with chronic obstructive pulmonary disease (COPD) is limited. To fill this gap, we studied the effectiveness of trivalent seasonal influenza vaccine (TIV) and 23‐valent pneumococcal polysaccharide vaccine (PPSV23), separately and together, at preventing adverse COPD outcomes. Methods: Our study used a self‐controlled, before‐and‐after cohort design to assess the effectiveness of TIV and PPSV23 in COPD patients. Patients were recruited from hospitals in Tangshan City, Hebei Province, China. Subjects self‐selected into one of the three vaccination schedules: TIV group, PPSV23 group and TIV&PPSV23 group. We used a physician‐completed, medical record‐verified questionnaire to obtain data on acute exacerbations of COPD (AECOPD), pneumonia and related hospitalization. Vaccine effectiveness was determined by comparing COPD outcomes before and after vaccination, controlling for potential confounding using Cox regression. Results: We recruited 474 COPD patients, of whom 109 received TIV, 69 received PPSV23 and 296 received TIV and PPSV23. Overall effectiveness for preventing AECOPD, pneumonia and related hospitalization were respectively 70%, 59% and 58% in the TIV group; 54%, 53% and 46% in the PPSV23 group; and 72%, 73% and 69% in the TIV&PPSV23 group. The vaccine effectiveness without COVID‐19 non‐pharmaceutical intervention period were 84%, 77% and 88% in the TIV group; 63%, 74% and 66% in the PPSV23 group; and 82%, 83% and 91% in the TIV&PPSV23 group. Conclusion: Influenza vaccination and PPSV23 vaccination, separately and together, can effectively reduce the risk of AECOPD, pneumonia and related hospitalization. Effectiveness for preventing AECOPD was the greatest. Abstract : We studied the effectiveness of trivalent seasonal influenza vaccine (TIV) and 23‐valent pneumococcal polysaccharide vaccine (PPSV23), separately and combined, at preventing acute exacerbations of chronic obstructive pulmonary disease (COPD), pneumonia and related hospitalization. TIV and PPSV23 vaccine combined appeared to reduce the incidence of adverse COPD outcomes most effectively. Separately or together, their effectiveness for preventing AECOPD was the greatest. On their own, TIV seemed more effective than PPSV23. See related Editorial